A rare case of hepatocellular carcinoma with right atrial invasion - Sandeep Murgi Babukumar; Vishwanth Kumbar; Gouri Kaveriappa; Ram Shenoy Basti; H B Suresh (Wolters Kluwer Medknow Publications, 2016)
An elderly male came with h/o loss of appetite and weight loss since 3 months. On evaluation, prothrombin time (PT), activated partial thromboplastin time (aPTT), and international normalized ratio (INR) values were high. Hepatitis B surface antigen (HbSAg) screening was reactive and serum alfa-fetoprotein (AFP) was raised. Ultrasound examination revealed a hepatic mass with inferior vena caval extension and direct invasion of the right atrium. Computed tomography (CT) scan of the lower thorax and abdomen was performed, which confirmed the ultrasound diagnosis. The patient had a brief stay in the hospital and got discharged against medical advice; he was not available for follow-up. Hepatocellular carcinomas (HCCs) commonly metastasizes to the lung, bone, brain, and adrenal glands. About 70% of the patients with HCCs have hepatic and portal vein invasions but encroachment into the right atrium is very rare. The most common symptoms of cardiac metastasis include asymptomatic cases, bilateral lower leg edema, and exertional dyspnea in that order. Typical complications of intravascular tumor extension lead to secondary Budd-Chiari syndrome, right heart insufficiency, or massive pulmonary embolism. The prognosis of HCC with atrial invasion is poor, with median survival ranging from 1 month to 4 months. HCC in these cases may be more aggressive, with a shorter doubling time. The risk for cardiopulmonary collapse is higher, with heart failure or sudden death. Surgical interventions as well as nonsurgical approaches have been used in the treatment of patients with symptomatic inferior vena cava (IVC)/right atrial tumor thrombi. There are few reports of en bloc hepatectomy and resection of the right atrial thrombus under cardiopulmonary bypass. Routine screening in patients with HCC, such as including chest imaging as part of surveillance computed tomographic scans, may facilitate earlier detection and treatment.